2022
DOI: 10.5713/ab.21.0435
|View full text |Cite
|
Sign up to set email alerts
|

Insect meal as a feed ingredient for poultry

Abstract: Shortage of protein feed resources is the major challenge to the world farm animal industry. Insects are known as an alternative protein source for poultry. A Wwide range of insects are available for use in poultry diets.Insect larvae thrive in manure, and organic waste, and produce antimicrobial peptides to protect themselves from microbial infections, and additionally these peptides might also be functional in poultry feed. The feed containing antimicrobial peptides can improve the growth performance, nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 103 publications
(222 reference statements)
1
34
0
Order By: Relevance
“…Sun et al [43] also observed an increase in total iron content of broiler chicken meat-fed grasshoppers compared to chicken meat without grasshopper inclusion in diets. The inclusion further improved the meat shelf life of broilers [7]. It could be concluded that various locust species are rich in iron, zinc, copper, and manganese.…”
Section: Grasshopper/locusts and Cricketsmentioning
confidence: 90%
See 2 more Smart Citations
“…Sun et al [43] also observed an increase in total iron content of broiler chicken meat-fed grasshoppers compared to chicken meat without grasshopper inclusion in diets. The inclusion further improved the meat shelf life of broilers [7]. It could be concluded that various locust species are rich in iron, zinc, copper, and manganese.…”
Section: Grasshopper/locusts and Cricketsmentioning
confidence: 90%
“…The grasshoppers, locusts, and crickets fall under the Orthoptera order [16]. It has been reported that insect meals from Orthoptera order contain high content of various essential nutrients including trace elements [7]. Insects from Orthoptera have higher iron that is readily available to maintain and balance iron in the body [18].…”
Section: Grasshopper/locusts and Cricketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, managing organic waste from the increasing human population is a concern [ 1 ]. From this perspective, insects are potential feed ingredients for poultry diets [ 2 ] and the black soldier fly ( Hermetia illucens , HI) is promising because it bioconverts organic waste into biomass [ 3 , 4 ], by storing protein and fat sources from organic waste decomposition during stage [ 5 ]. Hermetia illucens larvae (HIL) contain ~42% and 35% protein and fat sources, respectively [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elahi et al [ 2 ] introduced a wide range of insects including black soldier fly, mealworm, housefly, cricket/grasshopper/locust (Orthoptera), silkworm, and earthworm for potential use as feed ingredients in poultry because of rich essential amino acids and antimicrobial peptides when compared with conventional feedstuffs. The expectation is to improve the growth performance, nutrient digestibility, intestinal health, and immune function in poultry.…”
mentioning
confidence: 99%